LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK PROBLEM SOLVING UNTUK PENYESUAIAN SOSIAL SISWA SMP - Nabila, Viona Fara; Septian, Muhammad Rezza; Permana, Aditya (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This research highlights an important problem in the educational environment, namely the low social adjustment ability among class VIII students at SMAN 5 Cimahi. Using a Mix Method research method approach with an explanatory sequential design, this research aims to explore the effectiveness of group guidance services using problem solving techniques in improving students' social adjustment abilities. In a population of 120 students, the sample was selected using the simple random sampling method. Eight students were selected as the experimental group and eight other students as the control group. The research results show that group guidance services using problem solving techniques are effective in improving students' social adjustment abilities, as seen from the significant increase between the pre-test and post-test results. These results are also strengthened by statistical analysis, with significance values ​​indicating the effectiveness of applying problem solving techniques. The process of implementing group guidance services using problem solving techniques was considered successful, as seen from the interactive atmosphere and high enthusiasm created during the process. However, obstacles related to limited time for implementing services are a challenge for guidance and counseling teachers, while students face difficulties in opening up to each other. From these findings, it can be concluded that the group guidance approach with problem solving techniques has the potential to be a solution in improving students' social adjustment abilities in this school. However, it is necessary to consider ways to overcome the obstacles faced, such as more effective time management and building stronger social relationships among students.